2019
DOI: 10.3390/cryst9090475
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Dispersion of Nanoscale Particles on the Properties of Nematic Liquid Crystals

Abstract: This work reviews the recent progress made in last decade in understanding the role of dispersion ofnanoparticles and quantum dots into host nematic liquid crystals. There are two important ingredients of this work: Even a minute concentration of these non-mesogenic materials in host matrix can have reflective impact on the dielectric, electro-optical, and spectroscopic properties of host nematics and the nematic-nanoparticles composite systems become suitable for the use in nematic based display and other dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…A slight increase in the phase transition temperature in the region of small mass concentrations of nanoparticles in LC has already been observed in other similar systems. [45][46][47] In the study 48 it is assumed that this effect may correlate with the influence of the dipole moments of nanoparticles on the orientation order of LC, whereas in the study 49 the authors suggest that this process may be influenced by the stabilizer of colloidal nanoparticles, as well as nanoparticles shapes. The resulting nanoparticles have a shape close to spherical.…”
Section: Resultsmentioning
confidence: 99%
“…A slight increase in the phase transition temperature in the region of small mass concentrations of nanoparticles in LC has already been observed in other similar systems. [45][46][47] In the study 48 it is assumed that this effect may correlate with the influence of the dipole moments of nanoparticles on the orientation order of LC, whereas in the study 49 the authors suggest that this process may be influenced by the stabilizer of colloidal nanoparticles, as well as nanoparticles shapes. The resulting nanoparticles have a shape close to spherical.…”
Section: Resultsmentioning
confidence: 99%
“…This goal could be achieved by dispersion of quantum dots (QDs) into mixtures of MOMs as host nematic liquid crystals. This strategy affects the regularity of the crystalline phase, causing lower melting temperatures and sometimes induces positive effects also on the isotropization temperature of the nematic phases [66].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…The increase in Δε with an increase in concentration of CSQDs improved the molecular ordering in the doped systems, which consequently produced the phase difference between extraordinary and ordinary light rays. Thus, the birefringence of the pure and doped system is given as: Δn = ne − no (14) Here, ne and no are the refractive indices of extraordinary and ordinary rays, respectively. The schematic illustration of the optical model of birefringence has been depicted by Gupta et al [11].…”
Section: Electro-optical Parametersmentioning
confidence: 99%
“…Misra et al [13] explained the influence of dispersing Cu:ZnO in nematic MBBA liquid crystal and studied the dielectric properties and activation energies for the dispersed systems. Singh et al [14] reviewed the effect of doping nanoparticles in nematic liquid crystals. Rastogi et al [15] reported the effect of doping graphene oxide (GO) in negative ∆ε nematic p-methoxybenzylidene p-decylaniline (MBDA) liquid crystal and found that the rotational viscosity and threshold voltage increased with an increase in the concentration of GO in MBDA.…”
Section: Introductionmentioning
confidence: 99%